Earthquake exposures and mental health outcomes in children and adolescents from Phulpingdanda village, Nepal: a cross-sectional study - Schwind, Jessica S. (Child Adolesc Psychiatry Ment Health, 2018)
BACKGROUND: Mental health issues can reach epidemic proportions in developed countries after natural disasters, but research is needed to better understand the impact on children and adolescents in developing nations. METHODS: A cross-sectional study was performed to examine the relationship between earthquake exposures and depression, PTSD, and resilience among children and adolescents in Phulpingdanda village in Nepal, 1 year after the 2015 earthquakes, using the Depression Self-Rating Scale for Children, Child PTSD Symptom Scale, and the Child and Youth Resilience Measure, respectively. To quantify exposure, a basic demographic and household questionnaire, including an earthquake exposure assessment tool for children and adolescents, was created. RESULTS: Of the 62 respondents interviewed, 3.23% and 4.84% displayed symptomatology of depression and PTSD. A large number of respondents interviewed scored high for resiliency (80.65%). All 62 respondents were displaced from their household and witnessed severe damage of both their homes and village. The number of earthquake exposures had a strong, positive correlation with PTSD symptomatology. CONCLUSIONS: Although the number of respondents who showed signs of depression and PTSD symptomatology was lower than anticipated, resilience scores were considerably higher. Future research should explore which protective factors may contribute to high resiliency in Nepali children and adolescents. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13034-018-0257-9) contains supplementary material, which is available to authorized users.